Interactive map for public health service in Perlis / Muhamad Zharfan Mohd Zuki - Mohd Zuki, Muhamad Zharfan (2019)
Public health services in this country are having two categories which are private sector and government sector but for this study it only focuses on government sector. Malaysia is still lagging way behind in health care services for the poor as well as the affluent. In recent years, others country have upgraded on their quality services of public health and health management organizations. To achieve this in our country, the public health services needs to collaborate with Geographic Information System (GIS) and Adobe Flash application to deliver the best services to the public. This research was conducted with aim to develop an interactive interface for government public clinic in Perlis. This research was conducted to study the produce of interactive map for public health services by using Adobe Flash application. The GIS software was mainly used for data processing in order to analyst of network analysis. Afterwards, hotspot analysis will be conducted in order to support the network analysis. Besides that, develop an interactive map will be produce in order to visualize the services of public health in Perlis. Lastly, final output shows the interactive map includes the network analysis, hotspot analysis and also information about health. As conclusion, it hoped this study will help in improved the public health services provide and also can delivered quality services for public.